Perception of Sharia Banks Comparison Between Baby Boomers Generations and Millennial Generations - Ramlah, Ramlah; Bakri, Adzan Noor; Munir, Nurmaya Fitriani (Jurnal Iqtisaduna, 2020)
The objectives of this study are 1) To find out the description of the perception of baby boomers about sharia banking; 2) To find out the description of millennial generation perceptions about Islamic banking; 3) To find out how to compare the perception of the two generations of Islamic banks. This writing uses a Descriptive Statistics Method that seeks to illustrate how phenomena that occur when conducting research. Data collection is done through the distribution of questionnaires/questionnaires by directly plunging into the field and given to the elderly and productive age communities. It was testing the research hypothesis using the Maan-Whitney U Test. This research shows that (1) the Baby boomers generation understands well about sharia banking, both in terms of knowledge, religiosity, profit sharing, facilities/services, and location of sharia banking. (2) Millennials better understand Islamic banking, both in terms of knowledge, religiosity, profit sharing, facilities/services, and location of Islamic banking. However, after testing the hypothesis, it was found that there were no differences in the perceptions of the two generations.